El programa reactiva Perú y su relación en el crecimiento de las empresas de la región Loreto desde las perspectiva del empresario 2020-2021 - López Macedo, María Josefa (2022)
In this research, the reactivate Peru program and the growth of companies in the Loreto region are studied from the perspective of the entrepreneur, considering the importance of the role of companies in the economy of the region, for the study the 4134 companies of Loreto were considered. who accessed the program and 104 entrepreneurs, using 2 data collection instruments, one of them subjected to statistical reliability, the research was of a descriptive quantitative approach and a non-experimental cross-sectional and correlational design. The work concluded that the level of access to the guarantee program of the national government Reactiva Peru of the companies of the Loreto region, is not very significant, representing 0.82% with reference to the number of companies at the Peru level and 1.29% in relation to the amount granted. by the program to the total country; the majority of businessmen, on average 56%, consider that the Reactiva Peru program in the Loreto region allowed a positive growth of the beneficiary companies, with a percentage of 26% that considers the opposite and 19% is undecided; There is no statistical relationship between the Reactiva Peru program and the growth of companies in the Loreto region, demonstrated in the Spearman's Rho correlation coefficient, which presents an indicator of 0.137, however, 74% of participants consider that the Reactiva Peru program it is an effective public policy.